Virulence-associated plasmids from Yersinia enterocolitica and Yersinia pestis. - Portnoy, D A (1981)
A 44-megadalton plasmid associated with virulence and Ca2+ dependence from Yersinia enterocolitica 8081 was compared at the molecular level with a 47-megadalton plasmid associated with Ca2+ dependence from Yersinia pestis EV76. The plasmids were found to share 55% deoxyribonucleic acid sequence homology distributed over approximately 80% of the plasmid genomes. One region in which the plasmids differed was found to contain sequences concerned with essential plasmid functions. Forty-five mutants of Y. pestis were isolated which had spontaneously acquired the ability to grow on calcium-free medium (Ca2+ independence). Of these mutants, 21 were cured of their 47-megadalton plasmid, whereas the remaining had either suffered a major deletion of the plasmid or had a 2.2-kilobase insertion located in one of two adjacent BamHI restriction fragments encompassing approximately 9 kilobases. The inserted sequence was found at numerous sites on the Y. pestis chromosome and on all three plasmids in the strain and may represent a Y. pestis insertion sequence element.